Race/Ethnicity, Primary Language, and Income Are Not Demographic Drivers of Mortality in Breast Cancer Patients at a Diverse Safety Net Academic Medical Center - Divya A. Parikh; Rani Chudasama; Ankit Agarwal; Alexandar Rand; Muhammad M. Qureshi; Taylor Ngo; Ariel E. Hirsch (International Journal of Breast Cancer)
Objective. To examine the impact of patient demographics on mortality in breast cancer patients receiving care at a safety net academic medical center. Patients and Methods. 1128 patients were diagnosed with breast cancer at our institution between August 2004 and October 2011. Patient demographics were determined as follows: race/ethnicity, primary language, insurance type, age at diagnosis, marital status, income (determined by zip code), and AJCC tumor stage. Multivariate logistic regression analysis was performed to identify factors related to mortality at the end of follow-up in March 2012. Results. There was no significant difference in mortality by race/ethnicity, primary language, insurance type, or income in the multivariate adjusted model. An increased mortality was observed in patients who were single (OR = 2.36, CI = 1.28–4.37, p=0.006), age > 70 years (OR = 3.88, CI = 1.13–11.48, p=0.014), and AJCC stage IV (OR = 171.81, CI = 59.99–492.06, p<0.0001). Conclusions. In this retrospective study, breast cancer patients who were single, presented at a later stage, or were older had increased incidence of mortality. Unlike other large-scale studies, non-White race, non-English primary language, low income, or Medicaid insurance did not result in worse outcomes.